Distinct in situ structures of the Borrelia flagellar motor - Kudryashev, Mikhail; Cyrklaff, Marek; Wallich, Reinhard; Baumeister, Wolfgang; Frischknecht, Friedrich (Journal of structural biology, 2010)
Bacteria can be propelled in liquids by flagellar filaments that are attached to and moved by flagellar motors. These motors are rotary nanomachines that use the electrochemical potential from ion gradients. The motor can spin in both directions with specific proteins regulating the direction in response to chemotactic stimuli. Here we investigated the structure of flagellar motors of Borrelia spirochetes, the causative agents of Lyme disease in humans. We revealed the structure of the motor complex at 4.6-nm resolution by sub-volume averaging of cryo-electron tomograms and subsequently imposing rotational symmetry. This allowed direct visualisation of individual motor components, the connection between the stator and the peptidoglycan as well as filamentous linkers between the stator and the rod. Two different motor assemblies seem to co-exist at a single bacterial pole. While most motors were completely assembled, a smaller fraction appeared to lack part of the C-ring, which plays a role in protein export and switching the directionality of rotation. Our data suggest a novel mechanism that bacteria may use to control the direction of movement.
Available online 21 August 2009
Gesehen am 17.05.2021